RESILIENCE OF CHRYSOTILE: AN APPROACH TO CHARACTERISTICS, ENVIRONMENTAL RISKS, HEALTH, AND LEGAL PROTECTION - Ribeiro Nunes, Antônio José (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
The use of mineral resources has accompanied man since antiquity. Today, society is served by mineral products, among these, chrysotile, a mineral that has placed Brazil as one of the world's major producers. The research problem presents the following question: what general conditions allow the maintenance of chrysotile mining and industrialization activity? The objective of this article is to demonstrate the legal conditions and characteristics of the ore that guarantee its operational survival, that is, the resilience of chrysotile in the face of technological, environmental and occupational risks in asbestos mining activities. Thus, to respond to the objectives of the study and the problem pointed out, we chose to conduct a bibliographic research based on theoretical foundations of authors, books, sites of public agencies, as well as analysis of ADI's of the Supreme Court. It was intended to demonstrate the legal conditions that guarantee the survival of chrysotile; operational risks; occupational effects and diseases caused to workers with prolonged exposure to the mineral. Even considering the entire history of negative effects on the environment and health, legal actions with the Supreme Court by the national confederation of industry workers - CNTI, have sought alternatives to maintain the activity, given the social and economic importance of chrysotile, justified by operational guidelines such as controlled extraction and inspections through environmental pollution tests, occupational evaluation, implementation of collective protection equipment and mandatory use of PPE.